Peran Guru Pendidikan Agama Islam Dalam Menanamkan Pendidikan Multikultural Berbasis Nilai-Nilai Kearifan Lokal - Supriyanto; Amrin (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2022)
This study aims to determine the role of Islamic Religious Education teachers in instilling multicultural education based on local wisdom values ​​in Indonesia State Junior High School 15 Surakarta. Method The research used is a descriptive qualitative method with data sources obtained from the principal, teachers, and students. The data analysis used is data collection, data reduction, data presentation, and concluding. Data collection techniques are observation, interviews, and documentation as for the analysis technique through the reduction stage, data presentation stage, and stage conclusion. The results of the study indicate that the role of Islamic Religious Education teachers in instilling multicultural education based on local wisdom values ​​in Indonesia State Junior High School 15 Surakarta is teachers as educators, motivators, facilitators, with multicultural education based on local wisdom in the form of values ​​of equality, tolerance, democracy, pluralism and human values ​​(morals). Planting multicultural education based on local wisdom values is also influenced by supporting factors, namely first, support from all parties, and secondly, the school facilities are adequate. While the inhibiting factor namely the lack of good cooperation between the school and parents and guardians in shaping the character and personality of noble character in children or students.